Difficulties of Implementing Online Learning in Kindergarten During the Covid-19 Pandemic Outbreak: Teacher's Perspective Review - Safrizal Safrizal; Resti Yulia; Dadan Suryana (Universitas Pendidikan Ganesha, 2021)
Policies related to changing face-to-face learning to online learning have become a tough job for education practitioners, especially Kindergarten teachers. This is what triggers various polemics in the world of education, especially at the kindergarten level. Problems related to online learning are not only about hardware but also the various skills of teachers in presenting learning videos. This study aims to expose various difficulties, causal factors, and the readiness of kindergarten teachers to carry out online learning. The research method used is descriptive quantitative, with the selection of samples selected through the quota sampling technique. The research instrument used in this study was a form that was sent via a google form link. Analysis of the data used in this study is quantitative descriptive statistics with percentage techniques. The results showed that the difficulty of implementing online learning in Kindergarten 40% of respondents stated that the difficulty of implementing online learning lies in the difficulty of collaborating with parents in helping learning from home, 20% stated difficulties in assessing child development, while 16% stated time effectiveness less learning. Meanwhile, the contributing factors were 40% stated that their parents were busy due to work, 32% stated that the learning support facilities were limited, and 12% stated that the learning objectives were not achieved. Can be concluded that the difficulty of online learning is caused by the coordination of teachers and parents who have different activities, so there is a lack of synergy in assisting children when carrying out online learning.